Teachers' Perceptions, Interaction Patterns And Strategies Towards Iranian EFL Students' Willingness To Communicate Or Reticence - Allahyar, Negah (2015)
This study is a classroom research adopting a qualitative case study design With supplementary quantitative analyses to investigate how the iranian efl teachers Create or obstruct opportunities to talk for willing to communicate (WTC) and Reticent students using different interaction patterns and strategies. Three iranian efl Teachers and their respective WTC and reticent students from a private language Institute participated in this study. The analysis of the data dealt with the amount of WTC .and reticent students' contributions.